2007
DOI: 10.1200/jco.2007.12.3323
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Pethema Trial of Alternating Bortezomib and Dexamethasone As Induction Regimen Before Autologous Stem-Cell Transplantation in Younger Patients With Multiple Myeloma: Efficacy and Clinical Implications of Tumor Response Kinetics

Abstract: Bortezomib alternating with dexamethasone is a highly effective induction regimen with low toxicity. The kinetic study has shown a high degree of heterogeneity in response and rapid effect from both agents, supporting the use of a short induction regimen before ASCT in MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
2
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 37 publications
2
77
2
5
Order By: Relevance
“…63,64 Bortezomib-based therapy is also associated with rapid responses typically occurring within the first two cycles of treatment. [60][61][62] In the SUMMIT and CREST trials, bortezomib treatment was found to lead to an overall response rate of 25 and 30% in patients with moderate and severe renal impairment, respectively, 65 whereas the toxicity was comparable to that of patients without renal impairment. In a subanalysis of the APEX trial, bortezomib was effective in patients with renal impairment, including those with severe renal impairment, 66 with response rates and time to response similar across all subgroups of patients with varying degrees of renal function.…”
Section: Bortezomibmentioning
confidence: 99%
See 1 more Smart Citation
“…63,64 Bortezomib-based therapy is also associated with rapid responses typically occurring within the first two cycles of treatment. [60][61][62] In the SUMMIT and CREST trials, bortezomib treatment was found to lead to an overall response rate of 25 and 30% in patients with moderate and severe renal impairment, respectively, 65 whereas the toxicity was comparable to that of patients without renal impairment. In a subanalysis of the APEX trial, bortezomib was effective in patients with renal impairment, including those with severe renal impairment, 66 with response rates and time to response similar across all subgroups of patients with varying degrees of renal function.…”
Section: Bortezomibmentioning
confidence: 99%
“…[60][61][62] The pharmacokinetics of bortezomib are independent of renal clearance and are not influenced by the degree of renal impairment; dose adjustments are not required for patients with renal insufficiency, but in patients undergoing dialysis, bortezomib should be administered after dialysis. Adverse events in patients undergoing dialysis are largely similar to those observed in controls and in those with mild-to-severe impairment, with the exception of renal and metabolic adverse events, which were found to be more common in patients undergoing dialysis.…”
Section: Bortezomibmentioning
confidence: 99%
“…22 Because of the limitations of our data set, it was not possible to discern an effect of differing induction regimens in this analysis, although published data in fact suggest that improved CR rates are more evident with the introduction of novel agents throughout the 2000s. [23][24][25][26] Alternatively, it is possible that this represents a technical issue of data collection and verification, as defining relapse as time points can be less definitive than defining death, features that underpin the calculation of PFS and OS, respectively. However, the reduced TTNT in 2005 compared with 1999 suggests that, in fact, the reduced time to relapse is clinically evident.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the mechanism of action of farnesyltransferase inhibitors in pediatric T-ALL requires further investigations, as confirmed by early studies that showed no correlation between the presence of Ras mutations and the response to tipifarnib. 6 In fact, even if farnesylation is the dominant class of post-translational modification that activates RAS, there are other types of prenylation not inhibited by farnesyltransferase inhibitors that allow RAS attachment to the cell membrane and its participation in signal transduction. 6 Indeed, we can suppose that tipifarnib activity in ETP-ALL cells is at least in part, even if not completely, explained by NF1 inactivation.…”
mentioning
confidence: 99%
“…6 In fact, even if farnesylation is the dominant class of post-translational modification that activates RAS, there are other types of prenylation not inhibited by farnesyltransferase inhibitors that allow RAS attachment to the cell membrane and its participation in signal transduction. 6 Indeed, we can suppose that tipifarnib activity in ETP-ALL cells is at least in part, even if not completely, explained by NF1 inactivation. More experimental data are needed to clarify the real sensitivity of ETP-ALL cells to tipifarnib.…”
mentioning
confidence: 99%